Feeding and nutrition in children with neurodevelopmental disabilities - Sullivan, Peter B. (Mac Keith Press, 2009)
Written by a multi-disciplinary team of paediatrician, dietitians, speech and language therapist and clinical nurse specialist * Highly practical guide for healthcare workers responsible for the nutritional needs of children with neurological impairment.